Co-precipitation technique for the preparation of ferroelectric BaBi2Ta2O9 - Dhage, S. R.; Pasricha, R.; Murugan, A. Vadivel; Ravi, V. (Materials Chemistry and Physics, 2006)
A simple co-precipitation technique had been successfully applied for the preparation of pure ultrafine single phase BaBi2Ta2O9 (BBT). Ammonium hydroxide and ammonium oxalate were used to precipitate Ba2+, Bi3+ and Ta5+ cations simultaneously. No pyrochlore phase was found while heating powder at 800 degrees C and pure BaBi2Ta2O9 phase was found to be formed by X-ray diffraction. Particle size and morphology was studied by transmission electron spectroscopy (TEM). The room temperature dielectric constant at 1 kHz is 350. The ferroelectric hysteresis loop parameters of these samples were also studied. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: Ceramics; Chemical synthesis; electronic material; ferroelectricity; Oxides